Analyzing Performance of Banks in India: A Robust Regression Analysis Approach - Mohammad Athar Ali; Asif Pervez; Rohit Bansal; Mohammed Arshad Khan (Discrete Dynamics in Nature and Society)
This research aims to analyze the impact of bank performance determinants on bank performance by applying robust regression analysis. For this, the relationship between return on assets and net interest margin with bank performance determinants has been discussed using robust regression. Robust regression offers a better and more realistic analysis owing to reducing the impact of outliers and influential data, and it is recommended for more precise results.